The Plant Cuticle: An Ancient Guardian Barrier Set Against Long-Standing Rivals - Arya, Gulab Chand; Sarkar, Sutanni; Manasherova, Ekaterina; Aharoni, Asaph; Cohen, Hagai (Frontiers in Plant Science, 2021)
The aerial surfaces of plants are covered by a protective barrier formed by the cutin polyester and waxes, collectively referred to as the cuticle. Plant cuticles prevent the loss of water, regulate transpiration, and facilitate the transport of gases and solutes. As the cuticle covers the outermost epidermal cell layer, it also acts as the first line of defense against environmental cues as well as biotic stresses triggered by a large array of pathogens and pests, such as fungi, bacteria and insects. Numerous studies highlight the cuticle interface as the site of complex molecular interactions between plants and pathogens. Here, we outline the multidimensional roles of cuticle-derived components, namely, epicuticular waxes and cutin monomers, during plant interactions with pathogenic fungi. We describe how certain wax components affect various pre-penetration and infection processes of fungi with different life styles, and then shift our focus to the roles played by cutin monomers that are released from the cuticle owing to the activity of fungal cutinases during early stages of infection. We discuss how cutin monomers can activate fungal cutinases and initiate the formation of infection organs, the myriad impacts of cuticle defects on the nature of plant-fungal interactions, along with the possible mechanisms raised thus far in the debate on how host plants perceive cutin monomers and/or cuticle defects to elicit defense responses.